2002
DOI: 10.1159/000058332
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Gene Association Studies in Sporadic Alzheimer’s Disease

Abstract: The genetics of Alzheimer’s disease (AD) is complex. Three genes (amyloid precursor protein, presenilin 1 and presenilin 2) have been described in the relatively rare, early-onset, autosomal dominant familial form of AD. In the common, non-familial (sporadic) late-onset AD, the major known genetic risk factor is the Ε4 allele of the apolipoprotein E (APOE) gene. However, at least half of the people who develop AD do not carry this allele, and not all people who do carry this allele develop AD even if they live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 155 publications
(127 reference statements)
2
29
0
Order By: Relevance
“…Additionally, cathepsins B and L demonstrated increased expression in RML-and ME7-infected mouse brains, respectively. An imbalance of cathepsins, a family of lysosomal proteases, has been associated with neurodegenerative diseases, including Alzheimer's disease and prion disease (2,11,12,13,56). Our observations of up-regulated cathepsin expression again confirmed these previous findings.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, cathepsins B and L demonstrated increased expression in RML-and ME7-infected mouse brains, respectively. An imbalance of cathepsins, a family of lysosomal proteases, has been associated with neurodegenerative diseases, including Alzheimer's disease and prion disease (2,11,12,13,56). Our observations of up-regulated cathepsin expression again confirmed these previous findings.…”
Section: Discussionsupporting
confidence: 89%
“…Specifically for dementia, 80 genes involved in 3 major pathways known to affect brain function were selected: A ␤ /lipid metabolism, oxidative stress and inflammation/apoptosis [2] . In addition, genes positioned within previously identified AD linkage peaks were also selected.…”
Section: Gene Selection and Genotypingmentioning
confidence: 99%
“…The association of apolipoprotein E (APOE) to Alzheimer's disease (AD) has been convincingly and repeatedly demonstrated in numerous studies [1] . Additional susceptibility genes for AD have been more elusive and studies aimed at identifying such genes have, prior to whole-genome approaches, mainly been focused on genes with a demonstrated or implied function related to de-mentia development or genes chromosomally positioned within linkage peaks correlated to AD [2,3] . However, genes implicated in other complex conditions could also potentially be relevant to dementia.…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies observed that MMV act as a potential effect against Al induced free radical generation of oxidative stress protein (HSP70) involved neuronal damage of nerve cells evidenced by histological studies [10]. Altmann et al [11] confirmed that Al causes considerable damage of cerebral function include learning memory impairment in rats was linked to develop Alzheimer's disease (AD) [12,13]. Exacerbation of normal aging related changes and neuronal apoptosis has played key factor for impairment learning memory and neurodegenerative disorders [14][15][16].…”
Section: Introductionmentioning
confidence: 98%